Beyond the Canopy Cover: A Comparative Mediation Analysis of Green Space Quality versus Quantity on Mental Well-being and Social Cohesion in High-Density Low-Income Neighborhoods - Jasmila Tanjung; Maya Enderson; Taufiq Indera Jayadi; Eva Naritawati; Nurul Hanifah; Maximillian Wilson (HM Publisher, 2025)
Introduction: Rapid urbanization in the Global South has precipitated a mental health crisis, particularly in high-density, low-income neighborhoods where environmental stressors are endemic. While the association between urban green space (UGS) and mental well-being is well-documented, a critical knowledge gap remains regarding the differential impacts of green space quantity (availability) versus quality (usability/biodiversity) and the mediating role of social cohesion. Methods: This cross-sectional study employed a comparative mediation analysis involving 1,240 residents across 15 high-density districts in Jakarta, Indonesia. UGS quantity was measured using satellite-derived Normalized Difference Vegetation Index (NDVI), while quality was assessed using the Quality of Public Open Space Tool (POST). Mental well-being was evaluated using the WHO-5 Index, and physiological stress was quantified via salivary cortisol. Structural Equation Modeling (SEM) was utilized to test the mediating pathways of social cohesion and physical activity. Results: UGS quality demonstrated a significantly stronger direct effect on mental well-being (β = 0.42, p < 0.001) compared to UGS quantity (β = 0.15, p < 0.05). Social cohesion fully mediated the relationship between UGS quality and well-being (Indirect Effect = 0.18, 95% CI [0.12, 0.25]), whereas salivary cortisol levels were inversely associated primarily with UGS quality (β = -0.33, p < 0.001). Conclusion: In resource-constrained urban environments, the quality of green space—defined by safety, amenities, and aesthetics—is a more critical determinant of public mental health than mere vegetative cover.